The science and ethics of antipsychotic use in children - Di Pietro, Nina; Illes, Judy; Berger, Mai (Academic Press, 2015)
The Science and Ethics of Antipsychotic Use in Children reviews the latest findings for the safety and efficacy of the rapidly rising incidence of antipsychotic use in children and examines tensions that are created by off-label use, both in clinical psychiatric practice and research. In the past ten years, the number of antipsychotics prescribed to children with psychiatric disorders has skyrocketed. Despite this rapid growth, most medications have been inadequately studied in children for safety or efficacy and many have serious adverse health. Measures are needed to ensure that the health.